Effects of interpregnancy interval on pregnancy complications: protocol for systematic review and meta-analysis - Gebremedhin, Amanuel Tesfay; Regan, Annette K; Malacova, Eva; Marinovich, M Luke; Ball, Stephen; Foo, Damien; Pereira, Gavin (BMJ open, 2018)
IntroductionInterpregnancy interval (IPI) is the length of time between a birth and conception of the next pregnancy. Evidence suggests that both short and long IPIs are at increased risk of adverse pregnancy and perinatal outcomes. Relatively less attention has been directed towards investigating the effect of IPI on pregnancy complications, and the studies that have been conducted have shown mixed results.This systematic review will aim to provide an update to the most recent available evidence on the effect of IPI on pregnancy complications.Method and analysisWe will search electronic databases such as Ovid/MEDLINE, EMBASE, CINAHL, Scopus, Web of Science and PubMed to identify peer-reviewed articles on the effects of IPI on pregnancy complications. We will include articles published from start of indexing until 12 February 2018 without any restriction to geographic setting. We will limit the search to literature published in English language and human subjects. Two independent reviewers will screen titles and abstracts and select full-text articles that meet the eligibility criteria. The Newcastle-Ottawa tool will be used to assess quality of observational studies. Where data permit, meta-analyses will be performed for individual pregnancy complications. A subgroup analyses by country categories (high-income vs low and middle-income countries) based on World Bank income group will be performed. Where meta-analysis is not possible, we will provide a description of data without further attempt to quantitatively pool results.Ethics and disseminationFormal ethical approval is not required as primary data will not be collected. The results will be published in peer-reviewed journals and presented at national and international conferences.PROSPERO registration numberCRD42018088578.